Gertrude Stein et l’écriture des voix - Cristina De Simone (Sillages Critiques)
This article offers a few questions and hypotheses on the relationship between writing and voice in Gertrude Stein’s research. Through a brief comparison between the American author’s poetics and the experiments that gave way to the earliest audio recording devices, we suggest there is a resemblance in the problématiques approached between literary practice and reflection, and the imaginary worldview specific to its time period – a resemblance which proves enlightening for the similarities as well as differences it reveals.